If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(y + -1) = c Reorder the terms: 3(-1 + y) = c (-1 * 3 + y * 3) = c (-3 + 3y) = c Solving -3 + 3y = c Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 3y = 3 + c Combine like terms: -3 + 3 = 0 0 + 3y = 3 + c 3y = 3 + c Divide each side by '3'. y = 1 + 0.3333333333c Simplifying y = 1 + 0.3333333333c
| 8x^2(4x^3+2x^2+3x+1)= | | -7(3x-4)=-49 | | 6(2x-1)=4x+18 | | (X-2)(x+6)=180 | | -3(1+5)+4=-104 | | 3-x/42 | | 5/7-3Y=-2 | | 6-5[4-(7y-2)]= | | -(2+x)=-3(x-2) | | -6(n+-2)+4(3+-6x)=-36 | | y=(x+9)m | | 4X^3/X^5=64 | | -6(n+-2)+4(3+-6x)=36 | | 2ln(x+2)=ln(x-1) | | 5f+7f+f= | | Y/85=6/10 | | .25x+.10y=2.85 | | 200x-.67=100x+81 | | 7n+16-5n=34 | | 5/2h15 | | r-1.2=11.5 | | 5x-8=7x+4 | | 9x/2-4=34 | | 3y-2y+1=0 | | (6k+2)-(3k-2)= | | 7^4/7^2 | | 1-7y+4=3y+14-7y | | 7/12×5/6 | | 3^7/3^3 | | R/18-8=-7 | | 8x-x=-40 | | K-5=-13 |